Evolution of increased competitive ability may explain dominance of introduced species in ruderal communities. Issue 3 (31st May 2022) - Hierro, José L.; Eren, Özkan; Čuda, Jan; Meyerson, Laura A.
Abstract: The evolution of increased competitive ability (EICA) hypothesis encapsulates the importance of evolution and ecology for biological invasions. According to this proposition, leaving specialist herbivores at home frees introduced plant species from investing limited resources in defense to instead use those resources for growth, selecting for individuals with reduced defense, enhanced growth, and, consequently, increased competitive ability. We took a multispecies approach, including ancestral and non‐native populations of seven weeds, as well as seven coexisting local weeds, to explore all three predictions (i.e., lower defense, greater growth, and better ability to compete in non‐native than ancestral populations), the generality as an invasion mechanism for a given system, and community‐level consequences of EICA. We assessed plant defenses by conducting herbivory trials with a generalist herbivore. Therefore, finding that non‐native populations are better defended than ancestral populations would lend support to the shifting defense (SD) hypothesis, an extension of EICA that incorporates the observation that introduced species escape specialists, but encounter generalists. We also manipulated water additions to evaluate how resource availability influences competition in the context of EICA and plant plasticity in our semiarid system. We found that non‐native populations of one study species, Centaurea solstitialis, were better defended, grew faster, and exerted stronger suppression on locals than ancestral populations, offering support to EICA through the SD hypothesis. The other species also displayed variation in trait attributes between ancestral and non‐native populations, but they did not fully comply with the three predictions of EICA. Notably, differences between those populations generally favored the non‐natives. Moreover, non‐native populations were, overall, superior at suppressing locals relative to ancestral populations under low water conditions. There were no differences in plasticity among all three groups. These results suggest that evolutionary change between ancestral and non‐native populations is widespread and could have facilitated invasion in our system. Additionally, although trading growth for shifted defense does not seem to be the main operational path for evolutionary change, it may explain the dominance of some introduced species in ruderal communities. Because introduced species dominate communities in disturbed environments around the world, our results are likely generalizable to other systems.